Pengembangan Media Edukasi Self-Monitoring Card untuk Monitoring Penatalaksanaan Diabetes Melitus Tipe 2 pada Pasien Rawat Jalan - Nafian, Nastaina Awim; Yuniarti, Yuniarti; Prihatin, Setyo; Jaelani, Mohammad; Ambarwati, Ria (JURNAL RISET GIZI, 2024)
Background: The success of a management in patients cannot be separated from monitoring. Therefore, a warning system is needed to monitor the management of diabetes mellitus. One way is to monitor the management of diabetes mellitus patients. Media Self-Monitoring Card is the development of control card media that contains educational materials as well as monitoring to monitor diabetes mellitus management independently. Media Self-Monitoring Card has the advantage that it is practical to use, self-based so that monitoring can be carried out intensely.Objective: Â Develop Self-Monitoring Card educational media for monitoring the management of type 2 diabetes mellitus in outpatients.Method: This research method is Research and Development (R &; D) with five stages of development, namely analysis, development, implementation, and evaluation (ADDIE). The media that has been created is then tested through validation tests by two material experts and two media experts. The cut-off point Content Validity Index (CVI) limit on material validation and media validation tests is at least 0.8. Media that have been declared viable by material experts and media experts will then be field-tested limited by ten random respondents selected according to predetermined criteria.Result: The Content Validity Index (CVI) value in the material validation test was 0.9. While the Content Validity Index (CVI) value in the media validation test is 0.87. Based on limited field trials, a percentage of 94.3% was obtainedConclusion: Self-Monitoring Card media is suitable to be used as a medium for education and monitoring of type 2 diabetes mellitus management in outpatients. For this reason, further research is needed to determine the effectiveness of education using the Self-Monitoring Card to monitor the management of type 2 diabetes mellitus.